2021
DOI: 10.34117/bjdv7n2-262
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Físico-Química De Águas Minerais Comercializadas Em Picos, Piauí, Brasil / Physical-Chemical Evaluation of Mineral Waters Marketed in Picos, Piauí, Brazil

Abstract: Avaliação da água, principalmente daquela destinada ao consumo humano, é de fundamental importância, já que esta é um dos principais veículos de doenças. A desconfiança sobre a água proveniente do sistema público de abastecimento é um dos principais fatores que levam à utilização de fontes alternativas, como a água envasada, no entendimento de que essa fonte é segura. Com isso há um aumento do consumo de água mineral, principalmente em garrafões de 20 litros, substituindo a água dos sistemas de abastecimento p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
0
0
1
Order By: Relevance
“…A high pH was expected for the spring water in the livestock area, as this spring has an outcrop with sensorially perceptible mineral characteristics. Water pH is affected by mineral salt contents in the water, as reported by Alencar et al (2020) and Ribeiro et al (2021). The low pH of water from springs in native forests and reforested areas may be associated with Water quality and surroundings for s ystemic management of springs in rural areas the acidic nature of the soil in the study microregion, as observed by Sisinno and Moreira (1996).…”
Section: Water Quality and Surroundings For S Ystemic Management Of S...mentioning
confidence: 55%
“…A high pH was expected for the spring water in the livestock area, as this spring has an outcrop with sensorially perceptible mineral characteristics. Water pH is affected by mineral salt contents in the water, as reported by Alencar et al (2020) and Ribeiro et al (2021). The low pH of water from springs in native forests and reforested areas may be associated with Water quality and surroundings for s ystemic management of springs in rural areas the acidic nature of the soil in the study microregion, as observed by Sisinno and Moreira (1996).…”
Section: Water Quality and Surroundings For S Ystemic Management Of S...mentioning
confidence: 55%
“…Por outro lado, deve-se considerar ainda a vulnerabilidade à contaminação a que as fontes de água natural ou subterrânea estão sujeitas, provocadas possivelmente por ação de origem antrópica [6][7][8]. Assim, os contaminantes inorgânicos que podem estar presentes na água são caracterizados como potencialmente tóxicos e prejudiciais à saúde do organismo por possuírem elevada toxicidade e não apresentarem função biológica conhecida no organismo, como: Al, As, Cd e Pb, entre outros.…”
Section: Introductionunclassified